Nitric oxide is reduced to HNO (azanone) by ascorbic acid, tyrosine, and other alcohols. A new route for azanone formation in biological media. - Suarez, Sebastian (2015)
The role of NO in biology is well established. However, an increasing body of evidence suggests that azanone (HNO), could also be involved in biological processes, some of which are attributed to NO. In this context, one of the most important and yet unanswered questions is whether and how HNO is produced in vivo. A possible route concerns the chemical or enzymatic reduction of NO. In the present work, we have taken advantage of a selective HNO sensing method, to show that NO is reduced to HNO by biologically relevant alcohols with moderate reducing capacity, such as ascorbate or tyrosine. The proposed mechanism involves a nucleophilic attack to NO by the alcohol, coupled to a proton transfer (PCNA: proton-coupled nucleophilic attack) and a subsequent decomposition of the so-produced radical to yield HNO and an alkoxyl radical. (Graph Presented).